Religious Tensions in Time and Space: The ‘Controversial’ Interfaith Dynamics in Indonesia - Maliki, Muhammad Ihram; Sabri, Zaharuddin Sani Ahmad; Keumala, Mahmuda Putri; Simbolon, Fransiscus Johan (Universitas Negeri Semarang, 2024)
Indonesia, with its diverse religious landscape, has long been a site of interfaith interaction, where religious tensions often intersect with historical, social, and political forces. The dynamics of these interfaith relations are shaped by both time and space, with ongoing contestations surrounding the boundaries of religious practice, identity, and coexistence. This paper examines the ‘controversial’ nature of interfaith dynamics in Indonesia, particularly focusing on the ways religious tensions manifest across different temporal and spatial contexts. By analyzing the shifting role of religious minorities, the impact of political policies, and the influence of local cultural contexts, the paper investigates how time and space contribute to the fluidity and volatility of interfaith relations in the country. The urgency of this research lies in the growing challenges Indonesia faces in balancing its pluralistic ideals with rising religious conservatism and exclusivism, which often escalate tensions. This study offers novel insights into the spatial and temporal dimensions of religious identity formation, showing how contested religious spaces—whether urban or rural—serve as battlegrounds for social, cultural, and political power. Furthermore, it contributes to the academic discourse on the role of religion in shaping national identity, highlighting how the intersection of historical legacies and contemporary religious practices in Indonesia creates an ongoing tension between harmony and conflict. Ultimately, this paper underscores the complexity of interfaith relations in Indonesia, offering a nuanced understanding of how time and space shape the contentious nature of religious coexistence.